Efektivitas Bimbingan Kelompok untuk Meningkatkan Penyesuaian Sosial Siswa SMK - Galih Waskito; Asrowi Asrowi; Ulya Makhmudah (Jurnal Psikoedukasi dan Konseling)
Abstract: This study aimed to test the effectiveness of group guidance in improving students' social adjustment in vocational high school students. This study used an experimental method with a nonequivalent control group design (nonequivalent pretest-posttest). The subjects in this study were 45 students with low pretest scores. In the implementation of the treatment, the research subjects were divided into two groups: the experimental group was given group guidance, and the control group was given information services as usual. The data collection technique used is a social adjustment questionnaire tested for validity and reliability. Data analysis in this study used the Mann-Whitney test. Based on the results of hypothesis testing, it can be seen that there is a difference in scores between the experimental group and the control group after giving treatment. The results can be concluded that group guidance is practical for improving the social adjustment of class X SMK students. Based on these results, it is hoped that further researchers can develop group guidance to be more comprehensive.